INTERNAL AUDIT EFFICIENCY AND PUBLIC SECTOR PERFORMANCE: A STUDY OF SELECTED MDAs IN KWARA STATE - Aminat Arike ARIYO-EDU; Ibrahim Ayodeji WOLI-JIMOH; Muhammed Lawal SUBAIR (Malete Journal of Accounting and Finance, 2024)
The challenges of preventing corrupt practices, the necessity for the advancement of good governance, and the need for the assurance of accountability and transparency necessitated sound internal audit practice. Thus, this study investigated the impact of internal audit on the effectiveness of public sector in Kwara State. A descriptive survey design was used for the study because of the characteristics of the population. The target population of the study was 102 senior audit staff from which a Sample size of 81 respondents were selected namely, Kwara State University, Federal Civil Service Commission, Ministry of Finance, General Hospital Ilorin, and Ministry of Housing and Urban Development. Primary data was sourced through the administration of well-structured questionnaire using five-points Likert scale to measure the question items. Simple Linear Regression was used for the data analysis with the aid of Statistical Package for Social Sciences (SPSS) version 23.0 and the results revealed that 93.9% increase in public sector management (β=0.939, t0.05>1.645), caused a unit change in internal audit efficiency (IAE) of the selected case study. Also, a change in internal audit procedures caused about 87.2% increase in public sector assets (β=0.872, t0.05>1.645). Further finding revealed that a unit change in internal audit support (IAS) caused about 79.4% increase in public sector management effectiveness (β=0.872, t0.05>1.645) at 5% level of significant. The study concluded that internal audit demonstrated effectiveness in safeguarding public sector assets, enhancing service delivery, and promoting financial accountability. The study, therefore, recommended that public sector management should continue to strengthen the internal audit system departments, ensuring they have the resources and autonomy needed to carry out their duties effectively.